HUBUNGAN REWARD ORANG TUA DENGAN SIKAP PERCAYA DIRI ANAK (Penelitian Kuantitatif Korelasional pada Anak Usia 5-6 Tahun di TK Islam Tirtayasa Serang-Banten) - Bita Febriyanti Fazrin; Isti Rusdiyani; Siti Khosiah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2018)
Confidence is an important thing for a child to climb the wheels of life. Confident crisis can be caused by many things, one of which is the self-confidence that is not nurtured early on. Confidence affects their mental development and character. Proper stimulation greatly determines the child’s confidence to walk the wheel of life. Parents are the first environment in generating child confidence and other potential. This study aims to examine and obtain data empirically about the relationship between parents’ reward with the confidence of children aged 5-6 years in the kindergarten Islam Tirtayasa Serang-Banten. The method used in this research is quantitative with correlational research design. The population in this study is 50 pairs of variables X and Y variables. Samples of 44 pairs of variables X and Y. Techniques of data collection using observation instruments and questionnaires. Based on the results of normality calculations on variables X and Y, it can be concluded that both data variables are normally distributed. Results of linear regression calculations obtained results v = -28.624 + 1.071X. For linearity test yield Fcount = -0.438 <2.19 = Ftabel, so it can be concluded that linear regression model. Hypothesis testing is done by using product moment correlation analysis with result rhitung = 0,760 and rtabel = 0,297. Thus it can be concluded that there is a relationship between the reward of parents with child confidence.